Bioreactor performance and microbial community dynamics in a production-scale biogas plant in northeastern China - Yamei, Gao; Anyi, Yang; Jun, Bao; Ruxia, Ma; Lei, Yan; Yanjie, Wang; Weidong, Wang (International Journal of Agricultural and Biological Engineering, 2017)
In cold regions, heating is necessary to maintain the continuous and steady year-round operation of biogas fermentation. In this study, changes in the liquid composition, biogas production, and microbial diversity in heated- and unheated-phase samples were evaluated in a production-scale biogas plant that was fed continuously with cattle manure as a mono-substrate in Heilongjiang province in northeastern China. The volatile solid (VS) and volatile fatty acid (VFA) contents both gradually decreased in the heated and unheated fermentation processes. The chemical oxygen demand (COD) removal efficiency in the unheated phase sampled on June 15 (s-6-15) and October 15 (a-10-15) and in the heated phase sampled on January 15 (w-1-15) was 63.35%, 44.2% and 44.0%, respectively. The biogas production yields were in agreement with the results obtained for the VS and VFA contents and COD removal efficiency. The performance of the reactor in the heated phase was less efficient than that in the unheated phase, and the biogas production efficiency in June-August was higher than that in the other months. However, the CH4 content in the biogas remained similar all year. Moreover, ARDRA (Amplified Ribosomal DNA Restriction Analysis) was used to study the microbial community composition in the fermentation process. The results showed that the methanogenic archaeal consortium consisted mainly of members of the genera Methanomicrobiales and Methanosarcinales. In the heated phase, hydrogenotrophic methanogens represented the dominant methanogen in w-1-15 feedstock. After fermentation, the strict aceticlastic methanogen Methanosaeta became the dominant methanogen. In the unheated phase, the hydrogenotrophic methanogens and aceticlastic methanogens were equivalent in s-6-15 feedstock and effluent, and aceticlastic methanogens were dominant in both a-10-15 feedstock and effluent. Assessments of the bacteria diversity of the microbial communities revealed that the common strains in the feed and effluent of the three samples included the rumen bacteria, Bacteroides, Clostridium, Ruminococcaceae and Proteobacteria. Keywords: biogas production, production-scale plant, dairy manure, microbial community, northeast of China DOI: 10.3965/j.ijabe.20171001.2025 Citation: Gao Y M, Yang A Y, Bao J, Ma R X, Yan L, Wang Y J, et al. Bioreactor performance and microbial community dynamics in a production-scale biogas plant in northeastern China. Int J Agric & Biol Eng, 2017; 10(1): 191－201.